THE POLITICAL AND MILITARY DEVELOPMENTS IN BAHDINAN AREA 1988-1991 A HISTORICAL AND POLITICAL STUDY - Tawfiq, Sulaiman; Tawfiq, Hoger Tawfiq (Humanities Journal of University of Zakho, 2026)
From 1988 to 1991, among the most sensitive developments that appeared in Iraq, as a result of the Iraqi military operation against the Kurdish people, the political and military situation of Bahdinan area became most sensitive generally. Hence, during that time a political vaccum appeared in that area, the Kurdish forces did not have much power to suppresses Iraqi forces from their attacks, nonetheless, the Kurdish parties moved inside border as a partisan group to assess the region, to reorganize its clandestine organization and conduct partisan activities against the Iraqi forces in that area particularly after appearing political development because of Iraqi’s attack on Kuwait. These political and military developments that happened in the region during that time became unclear, therefore, this study attempts to depict this sensitive stage deeply. The main objective of this study is to show these developments that heppaned as a result of the political and military of Iraq in the region, likewise, to demonstrate the Kurdish and Kurdish political parties’ conditions, as the political development that were emerged in the region brought a golden opportunity for Kurdish parties to reorganize their organization and political activities also directly effected on the people’s feeling to conduct partisan activities against Iraqi forces. Within its writing, this article attempts to answer some related questions, such as how did the Anfal campaigns affect the Kurdish parties’ organization? how did Kurdish parties’ attempt to conduct political activities against Iraqi forces? How did Iraq’s development effect its forces in that region and what strategy Kurds used to take advantageous from that developments? Did the Kurdish poltical parties attempt to take advantageous from that development? What was the Iraqi government reaction towards these developments which happened in the region